Use of natural antioxidants in refined palm olein during repeated deep-fat frying - Jaswir, Irwandi; Che Man, Yaakob; Kitts, David D. (Elsevier Science, 2000)
An optimization study on the use of oleoresin rosemary extract, sage extract and citric acid added into refined, bleached and deodorized (RBD) palm olein before deep-fat frying of potato chips was performed using a constrained mixture design. Results revealed that the use of these natural antioxidants could improve the sensory acceptability of potato chips during a 5-day repeated deep-fat frying. All three antioxidants significantly (P < 0.05) improved the sensory characteristics, including appearance, taste, crispiness, odor and overall acceptability. After day 5 of frying, the most acceptable fried potato chips were those fried in oil containing a combination of 0.059% oleoresin rosemary extract, 0.063% sage extract and 0.028% citric acid. The natural antioxidants significantly (P < 0.05) lowered the rate of oxidation of oil during deep-fat frying and contributed to measured sensory acceptability of fried potato chips.